Assessment of the Impact of Higher Temperatures Due to Climate Change on the Mortality Risk Indexes in Ecuador Until 2070 - Montenegro, M.; Campozano, L.; Urdiales-Flores, D.; Maisincho, L.; Serrano-Vincenti, S.; Borbor-Cordova, M. J. (Frontiers in Earth Science, 2022)
Extreme weather conditions, including intense heat stress due to higher temperatures, could trigger an increase in mortality risk. One way to evaluate the increase in mortality risk due to higher temperatures is the high risk warming (HRW) index, which evaluates the difference between the future and base period of a given percentile of daily maximum temperature (Tmax). Another is to calculate the future increase in the number of days over the temperature of such percentile, named high risk days (HRD) index. Previous studies point to the 84th percentile as the optimum temperature. Thus, this study aims to evaluate HRW and HRD indexes in Ecuador from 2011 to 2070 over the three natural climate zones, e.g., Coast, Andes, and Amazon. This climate analysis is based on historical data from meteorological stations and projections from CSIRO-MK36, GISS-E2, and IPSL-CM5A-MR, CMIP5 global climate models with dynamical scale reduction through weather research forecasting (WRF). The representative concentration pathways (RCPs), 8.5, were considered, which are related to the highest increases in future temperature. The results indicate that HRW and HRD will experience a larger increase in the period 2041–2070 compared with the period 1980–2005; in particular, these two indices will have a progressively increasing trend from 2011 onward. Specifically, the HRW calculated from the CMIP5 models for all stations is expected to grow from 0.6°C to 1.4°C and 1.8°C to 4.6°C for 2010–2040 and 2041–2070, respectively. Also, it is expected that the HRD for all stations will increase from 42 to 74 and 120 to 227 warming days for 2011–2040 and 2041–2070, respectively. The trends derived using Sen’s slope test show an increase in the HRW between 0.5°C and 0.9°C/decade and of the HRD between 2.88 and 4.9 days/decade since 1985. These results imply a high increase in heat-related mortality risks related to climate change in Ecuador. In terms of spatial distribution, three Ecuadorian regions experienced more critical temperature conditions with higher values of HRW and HRD for 2070. As a response to the increased frequency trends of warming periods in tropical areas, urgent measures should be taken to review public policies and legislation to mitigate the impacts of heat as a risk for human health in Ecuador.